Задачи по элементарной математике - Лидский В. Б. Виктор Борисович; Овсянников Л. В. Лев Васильевич; Тулайков А. Н. Анатолий Николаевич; Шабунин М. И. Михаил Иванович; Федосов Б. В. Борис Васильевич (Москва, Наука, 1973)
Исключено из фонда НТБ ТПУ